Salvianolic acid A from Danhong Injection induces vasorelaxation by Regulating L-type calcium channel in isolated mouse arteries. (5th October 2022) - Lin, Yi-Ke; Chen, Yi-Jun; Li, Jie-Yi; Chen, Yu-Lin; He, Dong; Zuo, Rui; Xiao, Min-Jun; Xu, Dan-Ping; Zheng, Chao-Yang; Wang, Wei; He, Rong-Rong; Chen, Yang
Abstract: Ethnopharmacological relevance: Danhong injection (DHI), which is a Chinese clinical prescription consists of Radix et Rhizoma Salviae Miltiorrhizae ( Salvia miltiorrhiza Bge., Labiatae, Danshen in Chinese) and Flos Carthami ( Carthamus tinctorius L., Compositae, Honghua in Chinese)(Plant names have been checked with http://www.theplantlist.org on March 1st, 2022), has been mainly used in the clinical therapy of cardiovascular diseases, including hypertension in China for many years. Aim of the study: Cardiovascular diseases (CVDs) are the major causes of death all around the world. Due to the various stimulation, a series of vasoconstrictor substances are secreted to regulate the vasoconstriction function and then change blood pressure. The representative substances leading to abnormal vasoconstriction include renin-angiotensin system, endothelin, vasopressin and adrenaline, which act on the corresponding receptors on vascular smooth muscle to constrict blood vessels. Finally, blood pressure increases, followed by a series of cardiovascular diseases, including hypertension. However, little is known about Danhong injection's specific vasodilating mechanisms and active substances. The aims of the study were to determine the vasodilating substances of Danhong injectio n and explain its molecular mechanism of vasodilation. Materials and methods: The effects of DHI and its active components on vascular tension were measured by myograph system in the aortic or mesenteric rings of mice. Based on this, the pharmacodynamic substances were analyzed and effective molecules were found. Combined with multiple types of vascular myograph experiments and network pharmacological analysis, the molecular pathway was preliminarily determined. With molecular biology experiments, it was verified that the relevant mechanisms were closely related to calcium-mediated vasoconstriction in smooth muscle cells. Results: DHI could relax endothelium-removed aortic rings pre-constricted with PE and 3 possible active vasodilator substances, including salvianolic acid A, salvianolic acid B and danshensu, were screened out by network pharmacology and vascular myograph experiments, among which the effects of salvianolic acid A were dominant. Meanwhile, salvianolic acid A could dilate mesenteric artery in a pressure-dependent manner. Interestingly, salvianolic acid A could still relax the vascular rings under the stimulation of KCl and Bayk8644, two agonists of L-type calcium channel. By contrast, inhibitors of Kir, Kv, Katp and BKCa channels did not block the effect of salvianolic acid A on vasodilation. Salvianolic acid A alleviated Ca 2+ transient, referring to changes of intracellular calcium, induced by PE, Bayk8644 and high K + in the VSMCs. Salvianolic acid A could partially restore the vasodilation function of vascular smooth muscle damaged by AngII and ET-1 induced hypertension situation. Conclusions: Our results indicate that salvianolic acid A is the major vasodilator substance in DHI and the vasorelaxation pharmacology mechanism involved in inhibiting the L-type calcium channel signaling in smooth muscle cell. Hence, there are potential therapeutic effects of taking salvianolic acid A preparation which may be beneficial to protect cardiovascular system and reduce blood pressure. Graphical abstract: Image 1 Highlights: Salvianolic acid A was screened out from Danhong injection as a main vasodilator component with the shortest vasodilation time. Salvianolic acid A relaxes blood vessels mainly by inhibiting L-type calcium channel. Salvianolic acid A can restore the vascular function damaged by endothelin-1 and AngII to a certain extent.